Quantitative Assessment of Bone Marrow Activity Using 18F-FLT PET in Aplastic Anemia and Myelodysplastic Syndromes. (3rd December 2022) - Tasaki, Toshiki; Tsujikawa, Tetsuya; Hosono, Naoko; Mori, Tetsuya; Makino, Akira; Kiyono, Yasushi; Okazawa, Hidehiko; Yamauchi, Takahiro
Abstract : Purpose: Peripheral cytopenias are typical of blood test abnormalities associated with a variety of conditions, including aplastic anemia (AA) and myelodysplastic syndromes (MDSs). We prospectively investigated the feasibility of quantitative analysis of whole-body bone marrow activity using PET with 3′-deoxy-3′- 18 F-fluorothymidine ( 18 F-FLT) in AA and MDS. Patients and Methods: Sixty-eight patients with cytopenia underwent 18 F-FLT PET/MRI scan, with simultaneous bone marrow aspiration and biopsy for hematopoiesis evaluation. SUVs were measured in the vertebrae (Th3, 6, and 9 and L3), bilateral iliac crests, and extremities. SUV and bone marrow pathology were compared between AA and MDS and analyzed in relation to severity of AA and prognosis of MDS. Results: Of the 68 patients with cytopenia, 12 were diagnosed with AA, 27 with MDS, 12 with bone marrow neoplasia, 2 with myelofibrosis, and 15 with other conditions. Iliac 18 F-FLT SUVs were significantly correlated with bone marrow cell numbers and cell density ( r = 0.47, P < 0.001 and ρ = 0.65, P < 0.001, respectively). There was a significant positive correlation between iliac and vertebral SUVs in AA and MDS ( r = 0.65, P < 0.05 and r = 0.70, P < 0.001, respectively), and the slope of the regression line was significantly steeper in AA than in MDS ( P < 0.05). In AA patients, vertebral 18 F-FLT SUVs significantly decreased with disease progression, and in MDS patients, higher whole-body 18 F-FLT uptake was associated with shorter overall survival (hazards ratio, 3.18; 95% confidence interval, 1.07–9.47; P = 0.037). Conclusions: Quantitative whole-body bone marrow imaging using 18 F-FLT PET helps distinguish AA from MDS and assess the severity of AA and prognosis of MDS.